Bactericidal efficacy of mobile ultraviolet-C disinfection devices in reducing contamination in biosafety laboratories - Tao, Chunai; Tang, Xiaolan; Luo, Jiayi; Zhang, Xinbi (The Journal of Infection in Developing Countries, 2023)
Introduction: Biosafety research requires a wide range of microorganisms and thorough disinfection to prevent laboratory infection is often required. Ultraviolet-C (UV-C) exposure reduces bacterial and viral concentrations. Therefore, in this study, we aimed to evaluate the efficacy of a mobile UV-C device as a non-contact disinfection strategy. Methodology: The bactericidal efficacy of the UV-C device was determined based on log10 decreases in the relative abundances of bacterial indicators, including Escherichia coli, Staphylococcus aureus, Staphylococcus albus, and Pseudomonas aeruginosa at 0.5 and 1.0 m after irradiation for 30, 60, and 90 min. Next, the reduction of natural bacteria in air and on surface as a result of the UV-C device exposure in the laboratory were determined. Results: Exposure to the UV-C disinfection device resulted in mean log10 decreases in microbial contamination of 3.55 and 5.85 following irradiation for 30 and 90 min, respectively, at a distance of 0.5 m. Further, P. aeruginosa and E. coli were the most and least sensitive to UV-C exposure, respectively. The bacterial load in air decreased by 65.53% after 60 min of irradiation, while those on surfaces decreased by 44.19% and 78.23% after 30 and 60 min of irradiation, respectively. Conclusions: The UV-C device effectively reduced bacterial load after irradiation for over 60 min. Further studies are encouraged to determine the effectiveness of the UV-C disinfection device in frequently occupied institutions, such as primary medical, health, and nursery, and its efficiency in infection control.